2023
DOI: 10.1101/2023.03.20.532894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Unique Neural Signature of Your Trip: Functional Connectome Fingerprints of Subjective Psilocybin Experience

Abstract: The emerging neuroscientific frontier of brain fingerprinting has recently established that human functional connectomes (FCs) exhibit fingerprint like idiosyncratic features, which map onto heterogeneously distributed behavioural traits. Here we harness brain fingerprinting tools to extract FC features that predict subjective drug experience induced by the psychedelic psilocybin. Specifically, in neuroimaging data of healthy volunteers under the acute influence of psilocybin or a placebo, we show that, post-p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…However, similar to research on anxiety-related psychopathology, this work has produced several inconsistencies regarding which particular networks are impacted (Müller et al, 2018). Several studies have found that psychedelics acutely decrease connectivity within the DMN (Carhart-Harris et al, 2012Madsen et al, 2021;Mason et al, 2020;Müller et al, 2018;Palhano-Fontes et al, 2015;Timmermann et al, 2023) and decrease connectivity between the DMN and hippocampus (Carhart-Harris et al, 2014;Lebedev et al, 2015;Siegel et al, 2023;Tolle et al, 2023). In contrast, psychedelics may acutely increase connectivity between the DMN and SN (Carhart-Harris et al, 2013Madsen et al, 2021;Stoliker et al, 2023;Timmermann et al, 2023).…”
Section: Acute Effectsmentioning
confidence: 75%
“…However, similar to research on anxiety-related psychopathology, this work has produced several inconsistencies regarding which particular networks are impacted (Müller et al, 2018). Several studies have found that psychedelics acutely decrease connectivity within the DMN (Carhart-Harris et al, 2012Madsen et al, 2021;Mason et al, 2020;Müller et al, 2018;Palhano-Fontes et al, 2015;Timmermann et al, 2023) and decrease connectivity between the DMN and hippocampus (Carhart-Harris et al, 2014;Lebedev et al, 2015;Siegel et al, 2023;Tolle et al, 2023). In contrast, psychedelics may acutely increase connectivity between the DMN and SN (Carhart-Harris et al, 2013Madsen et al, 2021;Stoliker et al, 2023;Timmermann et al, 2023).…”
Section: Acute Effectsmentioning
confidence: 75%